Między metaforą a afektywnością. Ciało czujące w tekście - Przymuszała, Beata (Załącznik Kulturoznawczy, 2021)
This article discusses the breakthrough of the change in talking about synesthesia. Highlighting the bodily aspect of imaging allows to combine the linguistic, psychological and artistic context. By discussing selected images from Myśliwski’s novel, the author shows how the material/sensual aspect of the description allows the recipients to feel the presented situation and at the same time rethink their own thinking (feel their own thinking).